2014
DOI: 10.1002/chem.201404421
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Assembly and Disassembly of Receptor‐Decorated Gold Nanoparticles Controlled by Ion Recognition

Abstract: The controlled assembly of randomly dispersed colloidal particles can provide access to materials with advanced optical and electronic properties while providing fundamental insights into self-assembly processes in nature and nanotechnology. Typically, self-assembled nanoparticles are prepared by exploiting electrostatic interactions, lithographic techniques, and covalently linked molecular scaffolds. This results in static morphologies that cannot be disassembled easily. On the other hand, having access to sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…1). 45 Aer extensive study, Jonathan L. Sessler and teammates concluded that unsubstituted C4Ps exist in four different conformations, analogous to calix [4]arene (Fig. 2).…”
Section: Structures and Stabilities Of Various Conformations Of Calixmentioning
confidence: 99%
See 3 more Smart Citations
“…1). 45 Aer extensive study, Jonathan L. Sessler and teammates concluded that unsubstituted C4Ps exist in four different conformations, analogous to calix [4]arene (Fig. 2).…”
Section: Structures and Stabilities Of Various Conformations Of Calixmentioning
confidence: 99%
“…To tune the binding ability of C4Ps (hosts) with their guests (anions), researchers worldwide have designed and synthesized various b-substituted calix [4]pyrrole derivatives. For example, in 2011, Sessler's group synthesized b-octaalkyl-substituted C4P derivative 15 using N-tosylpyrrolidine pyrrole and acetone in satisfactory yield (Scheme 2).…”
Section: B-substituted Calix[4]pyrrolesmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] One of the main aspects of this multi-disciplinary field of chemistry is the design and creation of unusual compounds based on these receptors and sensors for biological and inorganic cation and anion. [5][6][7][8] It is known that compounds containing allyl group are good starting materials for polymerization reaction [9][10][11][12] and chiral molecules receiving, [13][14][15] but there are only few examples of such reactions in supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%